2009
DOI: 10.1021/jm9014197
|View full text |Cite
|
Sign up to set email alerts
|

(1-(4-(Naphthalen-2-yl)pyrimidin-2-yl)piperidin-4-yl)methanamine: A Wingless β-Catenin Agonist That Increases Bone Formation Rate

Abstract: A high-throughput screening campaign to discover small molecule leads for the treatment of bone disorders concluded with the discovery of a compound with a 2-aminopyrimidine template that targeted the Wnt beta-catenin cellular messaging system. Hit-to-lead in vitro optimization for target activity and molecular properties led to the discovery of (1-(4-(naphthalen-2-yl)pyrimidin-2-yl)piperidin-4-yl)methanamine (5, WAY-262611). Compound 5 has excellent pharmacokinetic properties and showed a dose dependent incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Hematoxylin and eosin (H&E) and periodic acid-Schiff base (PAS) staining and scoring of lung tissues also showed that Dkk1 d/d mice had reduced inflammation and leukocyte infiltration compared to WT mice ( Figure 1G, 1H and 1I ). We also showed that airway resistance increase by HDM was notably decreased by using the Dkk-1 inhibitor, (1-(4-(naphthalen-2-yl)pyrimidin-2-yl)piperidin-4-yl)methanamine) (Pelletier et al, 2009) (WAY-262611) or in Dkk1 d/d mice ( Supplementary Figure 1F ). Taken together, our results demonstrate that lack of Dkk-1 protects the host from chronic type 2 cell-mediated immune responses in the HDM-induced asthma model.…”
Section: Resultsmentioning
confidence: 76%
“…Hematoxylin and eosin (H&E) and periodic acid-Schiff base (PAS) staining and scoring of lung tissues also showed that Dkk1 d/d mice had reduced inflammation and leukocyte infiltration compared to WT mice ( Figure 1G, 1H and 1I ). We also showed that airway resistance increase by HDM was notably decreased by using the Dkk-1 inhibitor, (1-(4-(naphthalen-2-yl)pyrimidin-2-yl)piperidin-4-yl)methanamine) (Pelletier et al, 2009) (WAY-262611) or in Dkk1 d/d mice ( Supplementary Figure 1F ). Taken together, our results demonstrate that lack of Dkk-1 protects the host from chronic type 2 cell-mediated immune responses in the HDM-induced asthma model.…”
Section: Resultsmentioning
confidence: 76%
“…To assess the effect of 'loss of function' of Dkk4, we utilized Dkk inhibitors WAY-262611 and IIIC3, which had previously been shown to inhibit Dkk1 or Dkk2 (Li et al, 2012;Pelletier et al, 2009). Either 2 µM WAY-262611 or 10 µM IIIC3 fully inhibited the binding of Dkk4-AP to HEK293 cells expressing Lrp6, as visualized by AP staining (Fig.…”
Section: Expression Of Dkk4 Transgene In Skin Arrests Further Growth mentioning
confidence: 99%
“…Screens for Wnt pathway antagonists have utilized luciferase-based TCF reporter elements (5,19,39,40), alkaline phosphatase-conjugated antibodies that recognize TCF/␤-catenin complexes (28), and differentiation-dependent promoters as readouts for hit compounds (53). Each of these methods assesses changes in downstream Wnt signaling.…”
Section: Targeting Wnt Signalingmentioning
confidence: 99%
“…There has been a recent increase in the number of published reports of Wnt pathway modulators (5,15,19,28,32,34,37,39,40,51,58). Many of the studies reflect the efforts of pharmaceutical companies in identifying Wnt active compounds using high-throughput screening approaches.…”
Section: Identification Of Small Molecule Wnt Pathway Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation